Is there a nocebo response that results from disease awareness campaigns and advertising in Australia, and can this effect be mitigated? - Benson, Stuart (Journal of medical ethics, 2018)
Direct-to-consumer advertising is banned in Australia, and instead pharmaceutical companies use disease awareness campaigns as a strategy to raise public awareness of conditions for which the company produces a treatment. This practice has been justified by promoting individual autonomy and public health, but it has attracted criticism regarding medicalisation of normal health and ageing, and exaggeration of the severity of the condition in question, imbalanced reporting of risks and benefits, and damaging the patient-clinician relationship. While there are benefits of disease awareness promotion, there is another possible adverse consequence that has not yet been rigorously considered: the possibility of inducing a nocebo response via the campaign. We will discuss the creation of a nocebo response in this context.